Utilization of Pineapple Peel (Ananas comosus) as a Basic Ingredient of Activated Charcoal (JURNAL PROTEKSI KESEHATAN, 2022)
Waste utilization in the era of globalization receives a lack of attention from the community, because lackness of public unawareness. Pineapple peel waste (Ananas comosus) can be produce activated charcoal. This study aims to produce activated charcoal from pineapple peel waste that meets SNI requirements, such as water level, ash level, and iodine absorption ability. This is a quantitative research with two repetitions.  The results show that the water and ash level of the charcoal was 0.0054% and 0.0010%, respectively. The iodine absorption ability was measured by titration using 0.1 N sodium thiosulfate solution. The iodine absorption ability was 365.6 mg/g utilizing a 1.2 ml titer. In conclusion, the parameters meet the requirement of SNI that stated the maximum moisture content, ash content, and iodine absorbability in active charcoal, was 15%, 10%, and 750 mg/g, respectively.